Cloning and characterization of vacuolar Na+/H+ antiporter gene promoter from wheat (Triticum aestivum) cv. Kharchia Local - GOYAL, ETIKA; SINGH, AMIT KUMAR; MAHAJAN, MAHESH M; KUMAR, ARUN; KUMAR, KANIKA (The Indian Journal of Agricultural Sciences, 2023)
Soil salinity is one of the significant abiotic stresses in plants. Few efficient stress-inducible promoters from plants, especially from monocotyledonous crops like wheat (Triticum aestivum L.) are available to drive stress-inducible expression of transgene. Therefore, an experiment was conducted at ICAR-National Institute for Plant Biotechnology, New Delhi, during 2017–18 to clone and characterize stress-inducible promoter from wheat. Results found a 418 bp long NHX1 promoter (TaUNHX) from a bread wheat landrace, Kharchia Local. In silico analysis of TaUNHX predicted several cis-acting regulatory elements, including CAAT, DOF, GATA motifs and some essential stress-responsive elements. To analyze the activity of TaUNHX, Agrobacterium-mediated transient GUS assay in tobacco (Nicotiana tabacum L.) leaves and stems was studied under various abiotic stresses like salt (300 mM NaCl), drought (20% PEG) and ABA (100 μM). Stress-responsive nature of this promoter can be used to drive the expression of transgene following exposure to various stresses. The study's finding has significant implications as the characterized promoter can be used to develop transgenics where the transgene expression can be induced following exposure to stress.